Family Environment and Emotional Intelligence on Self-Efficacy in PAI Learning: The Mediating Role of Spiritual Intelligence - Aguslani Mushlih; Adi Rosadi (Excelencia: Journal of Islamic Education & Management, 2026)
students in Sukaresmi Sub-district, where more than 65% of students show reluctance to participate actively in religious learning activities. This study aims to analyze the influence of family environment and emotional intelligence on self-efficacy in PAI learning with spiritual intelligence as a mediating variable. A quantitative approach with a correlational design was employed, involving 250 junior high school students selected through proportional stratified random sampling. Data were collected using validated questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that emotional intelligence has a significant positive effect on spiritual intelligence (β = 0.856, p < 0.001) and self-efficacy (β = 0.356, p = 0.005). Spiritual intelligence significantly affects self-efficacy (β = 0.496, p < 0.001) and mediates the relationship between emotional intelligence and self-efficacy (β = 0.425, p < 0.001). However, family environment does not significantly affect spiritual intelligence or self-efficacy. The model explains 74.0% of the variance in self-efficacy with strong predictive relevance (Q² = 0.659), confirming that spiritual intelligence plays a crucial mediating role in translating emotional intelligence into self-efficacy in PAI learning